Interconnections among Homelessness, Family Separation, and Mental Health: Implications for Multi-Sectoral Social Services. Issue 45 (8th August 2019) - Shaikh, Arshi; Rawal, Hiren
Abstract: This qualitative study explored the interconnections among the phenomena of homelessness, family separation, and mental health and substance abuse issues within the social services, geographic, and infrastructure context of northern Ontario. In-depth semi-structured interviews were conducted with thirteen participants. Findings revealed the effects of colonization in the form of poor and overcrowded housing conditions in the northern First Nations, difficulties in obtaining affordable and suitable housing in northern towns and cities, reliance on the scarce social services for survival, and valiant attempts to cope with the cold climate of northern Ontario. All participants reported multiple and intergenerational experiences of separation from family due to involvement of child welfare system, placement in residential schools, death of family member(s), flooding, and epidemics. Participants described their lifelong struggles with mental health and substance abuse issues. All three phenomena were tied together in various configurations of causes and consequences. The implications include the need for critical examination of the historical policies and practices, early intervention for mental health and substance abuse issues, greater support for youth transitioning out of care, creation of a continuum of housing options, collaboration across multiple social services sectors, and incorporation of Indigenous worldview and practices in the mainstream services.